Defending Mao’s Dream: How Politicians’ Ideological Imprinting Affects Firms’ Political Appointment in China - Wang, Danqing; Du, Fei; Marquis, Christopher (Academy of Management Journal, 2019)
Prior studies on corporate political strategies have taken an exchange view to examine these strategies’ benefits and costs for firms and politicians, but have paid less attention to how politicians’ political values shape their perceptions of, and willingness to engage in, these exchanges. We investigate how politicians’ imprinted political ideologies affect the likelihood of firms’ political appointments. Examining 760 city mayors across 242 Chinese cities from 2001 to 2013, we find that cities have fewer private firms appointed to local councils if the mayor—the key decision maker for such appointments—is more strongly imprinted with an orthodox communist ideology that opposes capitalism. The intensity and evolution of such an ideological imprint are influenced by contextual factors. The imprint’s strength is shaped by the mayors’ prior exposure to intense ideological experiences, such as experiencing the Cultural Revolution at a young age. Working in an environment consistent with the ideology (e.g., a province with a greater communist legacy) sustains and even strengthens the imprint, whereas working in an environment inconsistent with the ideology (e.g., a city with greater economic development) attenuates it. We discuss the implications of these findings for political strategy research, imprinting theory, and nascent research on political ideology.